Ferroelectric, Analog Resistive Switching in Back‐End‐of‐Line Compatible TiN/HfZrO4/TiOx Junctions. Issue 5 (15th January 2021) - Bégon-Lours, Laura; Halter, Mattia; Popoff, Youri; Offrein, Bert Jan
Abstract : Due to their compatibility with complementary metal–oxide–semiconductor technologies, hafnium‐based ferroelectric devices receive increasing interest for the fabrication of neuromorphic hardware. Herein, an analog resistive memory device is fabricated with a process developed for back‐end‐of‐line integration. A 4.5 nm‐thick HfZrO4 (HZO) layer is crystallized into the ferroelectric phase, a thickness thin enough to allow electrical conduction through the layer. A TiO x interlayer is used to create an asymmetric junction as required for transferring a polarization state change into a modification of the conductivity. Memristive functionality is obtained, both in the pristine state and after ferroelectric wake‐up, involving redistribution of oxygen vacancies in the ferroelectric layer. The resistive switching is shown to originate directly from the ferroelectric properties of the HZO layer. Abstract : An analog resistive memory device is fabricated with a back‐end‐of‐line compatible process. Two TiN electrodes are separated by a ferroelectric, 4.5 nm‐thick HfZrO4 (HZO) layer, and a semiconducting TiO x interlayer. Synaptic functionality is obtained, in the pristine state as well as after wake‐up, and originates from the ferroelectric properties of the HZO layer.